1998
DOI: 10.1103/physrevlett.81.677
|View full text |Cite
|
Sign up to set email alerts
|

Coulomb Blockade Peak Spacing Fluctuations in Deformable Quantum Dots: A Further Test of Random Matrix Theory

Abstract: We propose a mechanism to explain the fluctuations of the ground state energy in quantum dots in the Coulomb blockade regime. Employing the random matrix theory we show that shape deformations may change the adjacent peak spacing distribution from Wigner-Dyson to nearly Gaussian even in the absence of strong charging energy fluctuations. We find that this distribution is solely determined by the average number of anti-crossings between consecutive conductance peaks and the presence or absence of a magnetic fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 20 publications
(29 reference statements)
5
53
0
Order By: Relevance
“…Within such sequences one may find in-phase resonances and/or strong correlations of the conductance peak heights. Vallejos, Lewenkopf, and Mucciolo [53] showed that shape deformations may change the spacing distribution of Coulomb blockade peaks. Stopa [54] demonstrated shape deformations in self-consistent calculations of the dot confining potential.…”
Section: Deformationsmentioning
confidence: 99%
“…Within such sequences one may find in-phase resonances and/or strong correlations of the conductance peak heights. Vallejos, Lewenkopf, and Mucciolo [53] showed that shape deformations may change the spacing distribution of Coulomb blockade peaks. Stopa [54] demonstrated shape deformations in self-consistent calculations of the dot confining potential.…”
Section: Deformationsmentioning
confidence: 99%
“…However, these approaches, which are valid at small r s (high densities), cannot easily explain the large widths (∼ 8∆) of the latest experiments [7]. A refined RMT approach [13], which accounts for shape deformations of the dot while adding electrons, explains the Gaussian profiles, while the widths remain comparable with ∆.…”
mentioning
confidence: 99%
“…Two main effects occur: (1) the peak heights fluctuate from peak to peak because of varying coupling between the wavefunction in the nanoparticle and the leads, and (2) the spacings between the peaks fluctuate because of interference contributions to the ground state energy. Peak heights have been studied first theoretically [9][10][11][12][13][14][15][16][17][18][19] and then experimentally [19][20][21]; agreement is good once effects of temperature [13,19] and classical dynamics [16][17][18] are taken into account.…”
Section: Introductionmentioning
confidence: 99%